The Impact of Dental Neglect on Oral Health Among 16-30-Year-Olds in Dhulikhel, Kavrepalanchok, Nepal - Mahanta, Swagat Kumar; Humagain, Manoj; Upadhyaya, Chandan; Prajapati, Dilip; Srii, Ritesh (Journal of Nepalese Society of Periodontology and Oral Implantology, 2021)
Introduction: Oral health status is linked to oral health behaviour and dental neglect can be an important parameter for assessment of oral health status. Such evaluation will help in providing and planning appropriate health promotion activities to target population. Objective: To assess socio-demographic variations in Dental Neglect (DN) and to determine the association between DN and oral health. Methods: Analytical cross-sectional study done at dental hospital in Dhulikhel from September-November 2020. A sample of 327 aged 16-30 years were selected by convenience sampling technique. Demographic details along with DN were collected through the DN questionnaire. Both self-reported oral health and oral health status were assessed. Oral health status was determined by using the Oral Hygiene Index-simplified (OHI-S) and the Decayed Missing Filled index (DMFT). Results: Majority 170 (52%) of the sample were from high DN group. A total of 187 (57.2%) of the participants rated their oral health status as all right. Higher number of participants were seen in the fair group of oral hygiene status. Significant correlations were found between education and OHI-S scores. Mean DMFT score was 3.6±1.6 which had higher mean Decayed (D) component as compared to the Missing (M) and Filled (F) components in the index. Conclusion: Dental neglect is present among the study population and is associated with self-reported oral health status. Disparities were observed between the socio-demographic variables and DN. The DN Scale can be used in dental health promotion and also in evaluation of health promotion interventions.